2008
DOI: 10.1038/bmt.2008.217
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological outcome in very young hematopoietic SCT recipients in relation to pretransplant conditioning

Abstract: Stem cell transplantation involves conditioning with TBI and/or intensive chemotherapy, which may cause longterm neuropsychological deficits, particularly in children treated at a very young age. The aim of this study was to investigate whether very young children who receive chemotherapy-based conditioning only (BUCY) may have a more favorable neuropsychological outcome than children conditioned with TBI-CY. Twenty-two children who underwent allogeneic SCT at 0.4-3.6 years of age were subject to an extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 28 publications
(54 reference statements)
3
46
1
Order By: Relevance
“…A previous study showed less favorable neurocognitive outcomes after sTBI when compared with BU. 39 Although both centers had very similar follow-up routines and all the leukemia patients were treated according to the common Nordic leukemia treatment protocols, we cannot completely rule out some differences in the local follow-up routines or changes over time. Some data were harder to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed less favorable neurocognitive outcomes after sTBI when compared with BU. 39 Although both centers had very similar follow-up routines and all the leukemia patients were treated according to the common Nordic leukemia treatment protocols, we cannot completely rule out some differences in the local follow-up routines or changes over time. Some data were harder to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…Research involving subgroups of patients with a CTBI can be challenging, though. Since cohorts of clinical paediatric groups often are small and heterogeneous, the statistical analysis gets complicated (Smedler & Winiarski, 2008). Further division into subgroups based on different moderators diminishes the groups even more, further diminishing statistical power.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Seizures are commonly seen after repetitive concussions (Saunders et al, 2009). Neurotoxic agents can result in significant cognitive impairment, for example from cancer treatment to the central nervous system (Smedler & Winiarski, 2008;Butler & Copeland, 2002) and from chronic exposure to alcohol during gestation (Green et al, 2009). Further factors that have been highlighted as having an impact on brain integrity are pre-term birth.…”
Section: Brain Reserve Capacitymentioning
confidence: 99%
“…This could be explained either by the circumstance that seven of the 11 patients with IOLs were found in the s-TBI group or by the fact that the TBI might have functionally impacted the brain and visual pathways (Hicks & D'Amato 1980;Locatelli et al 1993;Smedler & Winiarski 2008).…”
Section: Rb Visual Fieldsmentioning
confidence: 99%
“…It is well known that TBI can damage the developing brain (Locatelli et al 1993;Smedler & Winiarski 2008) and also busulfan has been reported to be neurotoxic, causing Electroencephalogram (EEG) abnormalities (La Morgia et al 2004). Cyclosporine A can cause abnormalities revealed by magnetic resonance imaging (MRI) or computerized tomography (CT) (Bartynski et al 2004) and has also been associated with papilloedema (Avery et al 1991;Walter et al 2000) and cortical blindness (Taque et al 2004).…”
Section: Introductionmentioning
confidence: 99%